Camera lucida : reflections on photography - Barthes, Roland (New York : Hill and Wang, 2010)
Camera Lucida, Roland Barthes's personal, wide-ranging, and contemplative volume--and the last book he published--finds the author applying his influential perceptiveness and associative insight to the subject of photography.

Commenting on artists such as Avedon, Clifford, Mapplethorpe, and Nadar, Barthes presents photography as being outside the codes of language or culture, acting on the body as much as on the mind, and rendering death and loss more acutely than any other medium.

This groundbreaking approach established Camera Lucida as one of the most important books of theory on the subject, along with Susan Sontag's On Photography
Prijevod djela: La chambre claire, note sur la photographie.
Keywords: Fotografija; Studije; Filozofsko gledište